The Use of Design Thinking in the Development of IoT Projects - Zainal, Salbiah; Yusoff, Rasimah Che Mohd; Abas, Hafiza; Ibrahim, Roslina; Ab. Rahim, Nor Zairah (Advances in Social Sciences Research Journal, 2024)
One of the difficulties in the teaching and learning of the Internet of Things (IoT) is the lack of exposure to IoT concepts and inadequate teaching methods and tools. The use of Design Thinking (DT) when developing IoT projects can promote solution-based thinking and enhance creativity in problem-solving. The process of DT involves five phases: Empathize, Define, Ideate, Prototype, and Test. The objective of this study was to evaluate the DT tools and process for developing IoT projects. This study involved 22 Information Technology undergraduate students. The Define Problem Statement template, POV template, User Feedback, and Affinity Diagram were among the DT tools introduced to the students. Using a survey form, each student assessed the efficacy of the DT tool and process. Student feedback revealed that the DT process and tools significantly enhanced their understanding of IoT projects. An expert assessment using a DT rubric was also carried out by a lecturer having a master’s degree in information and technology to assess students’ performance using five criteria. Students need to do two rounds of Affinity Diagram activity. The DT rubric results show students’ average scores increased from 2.52 to 3.48, indicating an improvement in students’ IoT project development using DT.